Understanding Women's Participation in Visual Inspection with Acetic Acid Screening: The Role of Characteristics, Behavior, and Psychological Factors Among Women of Reproductive Age - Zaim Anshari (Journal of Public Health Sciences, 2026)
The level of community health is shaped by four main determinants: environment, behaviour, health care, and heredity. Visual inspection with acetic acid (VIA) is a simple, low‑cost method that can be used for early detection of cervical cancer in primary care settings, yet uptake among women of reproductive age in Indonesia remains suboptimal. This analytic observational case–control study was conducted at Puskesmas Teladan, Medan, in 2025. A total of 102 women of reproductive age were enrolled, comprising 51 women who had undergone VIA (case group) and 51 women who had never undergone VIA but had heard about the test (control group). Data on socio‑demographic characteristics (age, education, occupation), behavioural factors (knowledge, attitude, practice), and psychological factors (perception, motivation) were collected using a structured questionnaire and analysed using chi‑square tests and multiple logistic regression. ​ In the multivariable model, good knowledge (adjusted odds ratio [AOR] 8.25; 95% confidence interval [CI] 2.32–29.36; p=0.001) and high motivation (AOR 15.92; 95% CI 5.35–47.42; p<0.001) were independently associated with undergoing VIA, whereas age, education, occupation, attitude, practice, and perception were not statistically significant. ​ Women of reproductive age with better knowledge about VIA and stronger motivation are substantially more likely to undergo VIA screening. Strengthening knowledge and intrinsic motivation through health promotion and counselling at primary health centres and via Posyandu cadres may increase uptake of VIA as an early detection strategy for cervical cancer.